A Portuguese language variety in Japan: Dekasegi Portuguese as a sociolect - Dall'Ava, Felipe (Confluenze. Rivista di Studi Iberoamericani, 2022)
Due to colonization and migratory movements, the Portuguese language can be found all over the globe. In Japan, it is mainly spoken by the Brazilian and other Latin American immigrant communities that have been established there since the early 1990s, in most cases, employed as a cheap workforce. Since then, this newly emerged Portuguese variety underwent a process of language change: in the vocabulary and phonology. In this paper, we would like to provide examples and arguments that support the idea that this language variety is a sociolect.